1983
DOI: 10.1002/j.1460-2075.1983.tb01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of HLA-DR mRNAs and cell surface antigens by interferon.

Abstract: Human interferons‐alpha, ‐beta and ‐gamma enhance HLA‐DR mRNAs in all the human lymphoblastoid and melanoma cell lines studied. The increase concerns both alpha and beta chain mRNAs. Moreover, we show that immune interferon‐gamma preferentially enhances class II MHC mRNA. This effect of IFN‐gamma on the synthesis of alpha and beta HLA‐DR chains has been also analysed by immunoprecipitation. It is abolished by a monoclonal antibody directed against human IFN‐gamma. The effect of interferon on the cell surface l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 22 publications
(11 reference statements)
3
42
0
Order By: Relevance
“…The HLA class I mRNA was induced 2 -3 times more in y-IFN-treated cells than in a-IFN-treated cells (cf. [7]) 6-16 mRNA was not induced significantly by y-IFN (Fig. 3 b), providing an examplc of a mRNA induced specifically by a-IFN.…”
Section: Induction Qf Mrnas By Y-ifnmentioning
confidence: 72%
See 2 more Smart Citations
“…The HLA class I mRNA was induced 2 -3 times more in y-IFN-treated cells than in a-IFN-treated cells (cf. [7]) 6-16 mRNA was not induced significantly by y-IFN (Fig. 3 b), providing an examplc of a mRNA induced specifically by a-IFN.…”
Section: Induction Qf Mrnas By Y-ifnmentioning
confidence: 72%
“…When the effects of a-and y-interferons were compared, the induced levels and kinetics were very similar for one mRNA (1-8) but were significantly different for the others. One mRNA (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) was induced more than 100-fold by a-interferon but not significantly by y-interferon. Parallel analysis of the level of c-myc mRNA showed it to decrease twofold in response to a-interferon, but to increase more than threefold in response to y-interferon, despite a more profound inhibition of cell growth by the latter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The two types of IFNs (␣␤ and ␥) bind to unique cell surface receptors, which induce the transcription of a number of distinct, but overlapping sets of genes (1)(2)(3). Among the genes that are inducible by both ␣␤ and ␥ IFNs are the MHC class I genes (1, 4 -7).…”
mentioning
confidence: 99%
“…[20][21][22][23] Indeed, our data showed that in vitro infection of AK7 cells with Ad.mIFN-g enhanced the expression of MHC antigens, more significantly class I antigens that are expressed at low levels by uninfected AK7 cells (Fig 2). Abundant CD4 + and CD8 + aggregates, which were not detected in PBS-and Ad.bgaltreated tumors, were present in Ad.mIFN-g-treated tumors of immunocompetent mice (Fig 7f-h).…”
Section: Discussionmentioning
confidence: 59%